Physiological control of elaborate male courtship: Female choice for neuromuscular systems - Fusani, Leonida (Neurosci Biobehav Rev, 2014)
Males of many animal species perform specialized courtship behaviours to gain copulations with females. Identifying physiological and anatomical specializations underlying performance of these behaviours helps clarify mechanisms through which sexual selection promotes the evolution of elaborate courtship. Our knowledge about neuromuscular specializations that support elaborate displays is limited to a few model species. In this review, we focus on the physiological control of the courtship of a tropical bird, the golden-collared manakin, which has been the focus of our research for nearly 20 years. Male manakins perform physically elaborate courtship displays that are quick, accurate and powerful. Females seem to choose males based on their motor skills suggesting that neuromuscular specializations possessed by these males are driven by female choice. Male courtship is activated by androgens and androgen receptors are expressed in qualitatively and quantitatively unconventional ways in manakin brain, spinal cord and skeletal muscles. We propose that in some species, females select males based on their neuromuscular capabilities and acquired skills and that elaborate steroid-dependent courtship displays evolve to signal these traits.